Innowacyjność drobiarstwa warunkiem jego konkurencyjności na europejskim rynku - Krawczyk, Józefa; Sokołowicz, Zofia; Ruda, Maria (Innovation in the Poultry Industry as a Condition of Its Competitiveness on the European Market, 2006)
The aim of the study is to present the possibility of supporting innovation in the poultry industry while accounting for the possible barriers to continued progress in this area.In a liberal economy, without outside support, the Polish poultry industry would be unable to introduce innovation that harmonizes the industry with the high EU standards. Thanks to the good use of preferential credits and EU funds (SAPARD, SPO, PROW), a several-fold increase in the export of poultry products to the EU market was observed within the first few months of EU integration. However, the European level of the poultry industry concentration was not attained despite the great progress achieved in this respect. Professional methods of marketing poultry products are still lacking. In the future, in addition to the fluctuating foreign currency exchange rate, these problems may become the greatest barrier to further development of the poultry industry.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 105-111